Quotient on some Generalizations of topological group - A. Muneesh Kumar; P. Gnanachandra; B. Ananda Priya (مجلة بغداد للعلوم)
In this paper, we define some generalizations of topological group namely -topological group, -topological group and -topological group with illustrative examples. Also, we define grill topological group with respect to a grill. Later, we deliberate the quotient on generalizations of topological group in particular -topological group. Moreover, we model a robotic system which relays on the quotient of -topological group.